A dual channel, quality-based price competition model for the WEEE recycling market with government subsidy. (March 2016) - Liu, Huihui; Lei, Ming; Deng, Honghui; Keong Leong, G.; Huang, Tao
Abstract: It is quite common to find both formal and informal sectors for processing waste electrical and electronic equipment (WEEE) in many emerging countries. Typically, the formal channel consists of recyclers with official qualifications for disassembling WEEE while the informal channel is dominated by unregulated recyclers. We develop a quality-based price competition model for the WEEE recycling market in a dual channel environment comprising both formal and informal sectors. The equilibrium acquisition prices and effects of government subsidy in the two channels are examined under four competitive scenarios. While government subsidy can support the formal sector, our analysis shows that at a higher quality level of waste, the marginal effect of subsidy is not as promising. When the quality of waste is high but the government subsidy is not substantial, the informal sector always has a competitive advantage. To promote the healthy development of the recycling industry the government should adjust the subsidy appropriately to limit the quality of waste at a high level suitable only for refurbishing in the informal sector. Our study also shows that both the formal and informal channels prefer high quality products. However, the informal recycler always has a better acquisition price to capture a bigger market share of used products than the formal recycler at the quality level of refurbishing for both recyclers. In a quality-pricing environment, as quality increases the acquisition prices in the two channels may crossover. This indicates that neither of the two channels always have a clear price advantage at all quality levels. We will not be able to obtain this result in a uniform pricing model. As such product quality is an important factor to consider in a competitive recycling market. Highlights: Develop a quality-based price competition model between formal and informal sectors. Examine the effects of government subsidy under four competitive scenarios. At higher quality level of waste, the marginal effect of subsidy is not as promising.